Validation of NeQuick TEC data ingestion technique against C/NOFS and EISCAT electron density measurements. Issue 7 (4th July 2016) - Nigussie, M.; Radicella, S. M.; Damtie, B.; Yizengaw, E.; Nava, B.; Roininen, L.
Abstract: This paper investigates a technique to estimate near‐real‐time electron density structure of the ionosphere. Ground‐based GPS receiver total electron content (TEC) at low and high latitudes has been used to assist the NeQuick 2 model. First, we compute model input (effective ionization level) when the modeled slant TEC (sTEC) best fits the measured sTEC by single GPS receiver (reference station). Then we run the model at different locations nearby the reference station and produce the spatial distribution of the density profiles of the ionosphere in the East African region. We investigate the performance of the model, before and after data ingestion in estimating the topside ionosphere density profiles. This is carried out by extracting in situ density from the model at the corresponding location of C/NOFS (Communication/Navigation Outage Forecast System) satellite orbit and comparing the modeled ion density with the in situ ion density observed by Planar Langmuir Probe onboard C/NOFS. It is shown that the performance of the model after data ingestion reproduces the topside ionosphere better up to about 824 km away from the reference station than that before adaptation. Similarly, for high‐latitude region, NeQuick 2 adapted to sTEC obtained from high‐latitude (Tromsø in Norway) GPS receiver and the model used to reproduce parameters measured by European Incoherent Scatter Scientific Association (EISCAT) VHF radar. It is shown that the model after adaptation shows considerable improvement in estimating EISCAT measurements of electron density profile, F 2 peak density, and height. Key Points: TEC ingestion into NeQuick 2 is found to be a good proxy for topside ionosphere electron density modeling NeQuick 2 after adaptation reproduces C/NOFS and EISCAT electron density measurements better than before adaptation Adapting NeQuick 2 to a GPS receiver TEC enables the model to estimate electron density in a better way for wide area